Achieving High Activity and Stability of Carbon Supported Pd-Cu Alloyed Catalysts for Fuel Cell Applications. Issue 13 (1st January 2019) - Gong, Qing; Gong, Shuiping; Zhang, Tengfei; Cheng, Xuan; Li, Hengyi
Abstract : The carbon supported palladium-copper alloyed catalysts (Pd-Cu/C) were synthesized by a facile two-step method with different molar ratios of Cu to Pd (Cu/Pd), namely, Cu/Pd = 2.0, 3.0, 4.0, and 5.0. The Cu nanoparticles were obtained by microwave assisted method, and followed by galvanic substitution of Pd on Cu nanoparticles. The as-prepared Pd-Cu/C exhibited mainly fcc phase with the average crystallite sizes ranging 4.0∼4.5 nm by varying Cu/Pd ratios of 2.0∼5.0. The degree of Pd-Cu alloying was significantly influenced by Cu/Pd ratios, which ultimately affected the activity toward oxygen reduction reaction (ORR) and stability of Pd-Cu/C. The best ORR activity with good stability was obtained for the Pd-Cu/C prepared with Cu/Pd = 4.0 owing to the formation of fcc PdCu alloy structure. The half-wave potentials (E1/2 ) reached 0.76 and 0.86 V (vs. RHE) in HClO4 and KOH solutions, respectively, which were comparable to those of commercial Pt/C, while the E1/2 values remained virtually unchanged after 1000 cycles. However, the limiting current density decreased by 12.7% in HClO4, resulted in 58.5% loss of electrochemical surface area due mainly to Pd-Cu dealloying. The maximum power densities of 315 and 181 mW⋅cm −2 were achieved with Pd-Cu/C at 0.10 mg Pd·cm −2 in the H2 /O2 and H2 /air single cells, respectively.